Lowered Cyclin E levels increase the efficiency and the specificity of capsaicin against cancerous cells of mesothelium - Cömertpay, Sabahattin; Gül í–zçelik Demirbanka, Fatma (Cellular and Molecular Biology, 2020)
Capsaicin is one of the most extensively studied phytochemicals and its cytotoxicity on various types of cancer has been demonstrated both in vitro and in vivo. The evaluation of its effect on mesothelioma, however, has remained quite limited. In this study, we investigated the anti-mesothelioma potential of capsaicin by observing its cytotoxicity on healthy, immortalized and cancerous cells of mesothelium in vitro and how this potential be affected by lowered Cyclin E levels, a key regulator of G1/S transition of cell cycle. For this purpose, we determined and compared the IC50 values of capsaicin in both FBS (Fetal Bovine Serum) containing and FBS-deprived medium of each cell population studied. Additionally, we examined the changes in both protein and mRNA levels of caspase-3 upon capsaicin exposure as well as conducted a series of experiments through which the relatively long term effect of capsaicin on the growth rate of the cells was assessed. As a result, the reduced Cyclin E obtained through the absence of FBS in growth medium was found not only to decrease IC50 values for all cell types dramatically (p<0.05) but also to cause a considerable difference between the values determined for cancerous and non-cancerous populations (p<0.05), which had not been observed in regular medium. Moreover, along with the fact that capsaicin exposure did not have an impact on the cell growth in long term in most cases, caspase-3 levels also remained the same when exposed to capsaicin, suggesting a mechanism of cell death independent of caspases.